Factors influencing subjective recovery of people with recent-onset psychosis: A cross-sectional study in a low-income Sub-Saharan country. (April 2019) - Temesgen, Worku Animaw; Chien, Wai Tong; Bressington, Daniel
Highlights: The levels of both subjective and clinical recovery in a low-income African country are found to be better than those reported in high-income countries. Individuals with higher quality of life were found to have significantly better subjective recovery level. Hopeless and centrally obese individuals are found to have significantly lower level of subjective recovery. Abstract: People with psychosis were traditionally believed to have a chronic deteriorating condition with no hope of recovery. Recent studies have shown varied levels of recovery across countries. However, evidence from low-income, particularly African countries is scant. This study aimed to investigate levels of subjective recovery of people with recent-onset psychosis and identify its influencing factors. A cross-sectional study was conducted among 263 outpatients with recent-onset psychosis in a low-income country, Ethiopia. Psychiatric outpatients were randomly selected, and assessed by a set of questionnaires measuring their psychosocial, clinical and physical health conditions. Hierarchical multiple regression tests were used to identify factors influencing subjective recovery. The level of subjective recovery was found to be high, with a mean Questionnaire about the Process of Recovery score of 44.17. Individuals with higher quality of life were found to have significantly better subjective recovery level. Hopeless and centrally obese individuals were found to have significantly lower level of subjective recovery. Despite the limitations associated with a cross sectional study design, the results suggest that individuals with recent-onset psychosis in Ethiopia may have a better level of subjective recovery than those in high-income countries and their recovery is influenced by quality of life, hopelessness and central obesity.